Protection of Public Services Personal Data in The Delivery of Public Services: Comparative Study in Indonesia and Malaysia - Tan, Winsherly; Karo Karo, Rizky Pratama Putra; Situmeang, Ampuan; Rusdiana, Shelvi; Razak, Siti Suraya Abd (SASI, 2025)
Introduction: Public service is essential in serving and engaging with the community. It is fundamental for building strong, resilient communities and ensuring a functioning democracy. However, the exposure of personal data in public service is worrying, as data breaches have affected the public's privacy.Purposes of the Research: This study examines the extent to which personal data is protected in the provision of public services in Indonesia and Malaysia. It also investigates how the Indonesian government can learn from Malaysia to improve its data protection in public services.Methods of the Research: This study employed a normative juridical approach. Secondary data was used in this study: the 1945 Constitution, Law Number 25 of 2009 concerning Public Services, Presidential Instruction Number 3 of 2003 concerning National Policy, Strategy for E-Government Development, and the Malaysian Personal Data Protection Act 2010.Results Main Findings of the Research: This study shows many data protection breaches in Indonesia. Additionally, no existing law protects personal data in Indonesia. It is recommended that Indonesia establish a law to protect the personal data of its citizens. Malaysia’s Personal Data Protection Act 2010 can be modelled to establish the law.